Students’ understanding in DC analysis of bipolar junction transistor circuits - Erawan Kurniadi; Jeffry Handhika; Purwandari Purwandari; Dhimas Kukuh P.A. (Universitas PGRI Kanjuruhan Malang, 2026)
This research investigates the depth of students’ understanding of fundamental circuit concepts, the characteristics of bipolar junction transistor (BJT), and their integration in solving DC transistor circuit analysis problems. Adopting a qualitative research design, the study involved undergraduate students enrolled in an introductory electronics course. The validity of the data was ensured through methodological triangulation employing comparative testing and Socratic dialogue. The comparative test consisted of two models: one focusing on current-strength comparisons and the other on voltage-level comparisons. The findings were verified and elaborated through Socratic dialogue using critical and exploratory questions to probe and test students’ ideas, assumptions, and beliefs. Data analysis and interpretation were facilitated through an integration matrix that aligned students’ comparative-test responses with their corresponding Socratic dialogues. Findings on the understanding in DC analysis of BJT circuits revealed three distinct categories of understanding: (1) Students who merely guessed answers without grasping either fundamental circuit principles or transistor behavior; (2) Students capable of performing mathematical analysis but lacking a sound conceptual understanding of transistor behavior; and (3) Students who could perform mathematical analysis and demonstrated a reasonable understanding of transistor behavior, yet still exhibited certain misconceptions. The findings imply the importance of fostering conceptual synthesis in BJT circuit analysis to enhance transferable problem-solving skills for analyzing more complex electronic systems and to support deeper analytical reasoning in electronics learning.